On Shehu Transform with Application of Solutions of Fractional Differential Equations - Bribesh, Fathi (Journal of Pure & Applied Sciences, 2023)
This review article explains the Shehu transform as a tool used for solving linear differential equations of fractional order, where the definition of the Caputo differential operator of order α>0, is taken into consideration. The transformation is used to convert Initial Value Problems (IVPs) of the fractional order of Caputo sense into simple algebraic equations. Then the inverse of the transform is used to obtain the analytical solution of the problem. We solved some illustrative examples.